Supporting activities of Yangtze Delta Zero Carbon Smart Village Alliance and summary report of 2025 alliance work for scaling up low carbon village practices - CGIAR Science Program on Climate Action (CGIAR System Organization, 2025)
The zero-carbon smart village is an innovative practice that deeply integrates the rural revitalization strategy with the goals of carbon dioxide peaking and carbon neutrality. It represents an innovation in the rural development model and is a response to contemporary propositions such as "harmonious coexistence between humanity and nature" and "integrated urban-rural development." Moreover, it provide a new green, smart, and shared prosperity-oriented example for rural revitalization in the context of the integrated development of the Yangtze River Delta region.